Sublingual immunotherapy tablets as a disease-modifying add-on treatment option to pharmacotherapy for allergic rhinitis and asthma. Issue 6 (18th August 2017) - Brunton, Stephen; Nelson, Harold S.; Bernstein, David I.; Lawton, Simon; Lu, Susan; Nolte, Hendrik
ABSTRACT: Allergic rhinitis (AR) with or without conjunctivitis (AR/C) is associated with a significant health and economic burden, and is often accompanied by asthma. Pharmacotherapies are the mainstay treatment options for AR and asthma, but guidelines also recommend allergy immunotherapy (AIT). Unlike pharmacotherapies, AIT has the ability to modify the underlying immunologic mechanisms of AR and asthma with the potential for long-term benefits after treatment is discontinued. Immunotherapy may also prevent progression of AR/C to asthma. Sublingual immunotherapy (SLIT)-tablets are a self-administered alternative to subcutaneous immunotherapy that provide the benefits of AIT without the cost and inconvenience of frequent office visits or the discomfort of injections. SLIT-tablets are also an option that can be utilized by primary care clinicians. Pharmacotherapies are generally effective in mild disease although a number of patients remain uncontrolled. SLIT-tablets have proven efficacy for AR in adults, children, and poly-sensitized allergic patients. Indirect comparisons indicate that SLIT-tablets have superior or comparable efficacy compared with traditional pharmacotherapies for seasonal AR, and superior efficacy for perennial AR. House dust mite (HDM) SLIT-tablets have also demonstrated clinically relevant benefits for asthma, with significant observed reductions in daily inhaled corticosteroid use, risk of asthma exacerbations, and asthma symptoms. SLIT-tablets are well tolerated, with minimal risk of systemic allergic reactions. The most common treatment-related adverse events are oral site reactions such as oral pruritus and throat irritation. Based on the favorable efficacy and safety profile, as well as the convenience of at-home oral administration and disease-modifying effects, SLIT-tablets should be considered as an alternative or add-on treatment to pharmacotherapy for AR/C, and as an add-on treatment for HDM allergic asthma.